ORP should not be used to estimate or compare concentrations of aqueous H2: An in silico analysis and narrative synopsis - LeBaron, Tyler W.; Sharpe, Randy (Frontiers in Food Science and Technology, 2022)
Oxidation reduction potential (ORP) has become a commonly used measurement to characterize functional beverages, specifically alkaline ionized water and hydrogen water. Numerous health benefits including antioxidant effects have been attributed to a negative ORP value. A greater negative ORP value is often incorrectly interpreted to mean a greater degree of health benefits and/or a high concentration of H2. Some hydrogen meters use the Nernst equation to calculate the concentration of H2 based on the measured ORP value. Unfortunately, due to the fundamental issues with the ORP meter, the calculated H2 value may be very inaccurate. Using the Nernst equation, we performed an in silico analysis of the ORP as a function of pH, temperature, and H2 concentration. Our analysis shows that a one unit increase in pH (e.g., 7–8) influences the ORP by as much as increasing the H2 concentration by 100 times (e.g., 1–100 mg/L). Similarly, at a saturated H2 concentration (1.57 mg/L) and pH 7, every ∆T of 20 °C changes the ORP by ≈ 30 mV. This is comparable to changing the H2 concentration by a factor of 10 (0.1 mg/L to 1 mg/L). Finally, to measure H2 within 0.1 mg/L, ORP meters need to have an accuracy of about 0.8 mV. However, ORP meters have an error range of at least ±10 mV, which corresponds to a potential error in measured H2 concentration of nearly 2 mg/L (≈125% error). This analysis shows that pH, temperature, and the intrinsic ORP errors can individually influence the ORP greater than the entire contribution of dissolved H2 within normally used ranges. In fact, this can easily result in a water sample with a greater negative ORP than another despite having significantly less H2. This makes it impossible to consistently determine if one water sample has more H2 than another water sample. Therefore, we can only conclude, based on a negative ORP reading, that, excluding the possibility of other reductive redox couples, some level of dissolved H2 is present in the water. Accordingly, ORP and ORP-based H2 meters are not recommended for testing or comparing the concentration of H2 in water. Experimental studies are warranted to determine if the ORP error is as great as or greater than what is predicted via this in silico analysis.